Analisis Kualitas Pelayanan dan Fasilitas dengan Metode SERVQUAL dan QFD di PT. SJKM - Yuli Setiawannie; Nita Marikena; Permadi, Akbar Rasyid (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
Service quality assessment is influenced by the perceptions and expectations of each customer which has an impact on customer satisfaction. PT SJKM is a service company for the sale of motorbikes, spare parts, and official motorcycle repairs from Yamaha. The number of complaints from customers about the company's services has resulted in a decrease in the number of customers, thus affecting the company's revenue. From these problems, this research was conducted to identify the company's service quality attributes by looking at the gap between customer perceptions and expectations, identifying service attributes that are in the critical category, and providing suggestions for improving company services. This research uses the SERVQUAL method to evaluate customer satisfaction from 33 service attributes. Furthermore, the QFD method to design improvement solutions for service attributes that are the main priority for improvement from the results of Importance Performance Analysis (IPA) analysis.  According to the research findings, there are 7 service attributes that are perceived negatively by customers, indicating their dissatisfaction. Out of the 6 service attributes that need improvement, dealer security is identified as the top priority and will be addressed first using the QFD method. Keywords: Customer Satisfaction, Importance Performance Analysis, QFD, SERVQUAL